2021
DOI: 10.3803/enm.2021.1111
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Machine Learning in Bone and Mineral Research

Abstract: In this unprecedented era of the overwhelming volume of medical data, machine learning can be a promising tool that may shed light on an individualized approach and a better understanding of the disease in the field of osteoporosis research, similar to that in other research fields. This review aimed to provide an overview of the latest studies using machine learning to address issues, mainly focusing on osteoporosis and fractures. Machine learning models for diagnosing and classifying osteoporosis and detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…ML essentially means that the computer itself learns patterns in the data and makes predictions on future data based on the patterns obtained. Current studies have shown that ML methods can be used to predict osteoporosis, and ML algorithms for osteoporotic risk assessment have shown the advantages of high accuracy and simplicity [ [51] , [52] , [53] , [54] , [55] ]. However, most of these studies have focused on predicting osteoporosis in older adults and postmenopausal women, and few reports have emerged to demonstrate the risk factors for diabetes-related fractures in China using ML algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…ML essentially means that the computer itself learns patterns in the data and makes predictions on future data based on the patterns obtained. Current studies have shown that ML methods can be used to predict osteoporosis, and ML algorithms for osteoporotic risk assessment have shown the advantages of high accuracy and simplicity [ [51] , [52] , [53] , [54] , [55] ]. However, most of these studies have focused on predicting osteoporosis in older adults and postmenopausal women, and few reports have emerged to demonstrate the risk factors for diabetes-related fractures in China using ML algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…A particular interest is observed in the field of total joint arthroplasty, where ML has been effectively employed in the analysis of tabular data, processing of medical imagery, and the interpretation of natural language. ML models are proficient in identifying fractures, classifying implant types in radiographic images, and discerning osteoarthritis stages through gait analysis [ 31 ]. Despite these promising developments and growing adoption of ML in orthopedics, several challenges persist.…”
Section: Reviewmentioning
confidence: 99%
“…23 Most studies using machine learning are cross sectional and examine the ability to identify persons with prevalent fractures or osteoporosis (BMD T-Score ≤ -2.5 SD). [24][25][26][27] This is the first prospective study using deep learning to derive an algorithm that identifies women having incident fractures during five years. The algorithm was developed by interrogating the three-dimensional images of bone and soft tissue, no other information was used.…”
Section: Many Qualities Of Bone Not Captured By Bmd But Not Yet Quant...mentioning
confidence: 99%
“…Application of Deep Learning to medical imaging 24 facilitates the investigation of bone's multilayered qualities and has been reported to identify patients with prevalent fractures or osteoporosis in cross sectional studies. [25][26][27] However, no prospective studies have applied deep learning using only the high resolution 3-dimensional images of bone and soft tissue to determine whether an algorithm, a Structural Fragility Score derived by Artificial Intelligence (SFS-AI), might capture deteriorated bone qualities and soft tissue.…”
Section: Introductionmentioning
confidence: 99%